Gender and workforce in urology – use of the BG index to assess female career promotion in academic urology - Jaque, Jenny; Wanke, Eileen M; Müller, Ruth; Bauer, Jan; Ohlendorf, Daniela; Mache, Stefanie; Klingelhöfer, Doris; Quarcoo, David (Urology Journal, 2020)
Purpose: Today, the majority of medical graduates in countries such as the UK, the US or Germany are female. This poses a major problem for workforce planning especially in urology. We here use first the first time the previously established Brüggmann Groneberg (BG) index to assess if female academic career options advance in urology. Methods: Different operating parameters (student population, urology specialist population, urology chair female:male (f:m) ratio) were collected from the Federal Office of Statistics, the Federal Chamber of Physicians and the medical faculties of 36 German universities. Four time points were monitored (2000, 2005, 2010 and 2015). From these data, female to male (f:m) ratios and the recently established career advancement (BG) index have been calculated. Results: The German hospital urology specialists’ f:m ratios were 0.257 (499 female vs. 1944 male) for 2015, 0.195 for 2010, 0.133 for 2005 and 0.12 for 2000. The career advancement (BG) index was 0.0007 for 2000, 0,0005 for 2005, 0.094 for 2010 and 0.073 for 2015. The decrease from 2010 to 2015 was due to an increase in the f:m ratio of hospital urologists and female medical students. Conclusion: The BG index clearly illustrated that there is an urgent need for special academic career funding programs to counteract gender problems in urology. The BG index has been shown to be an excellent tool to assess female academic career options and will be very helpful to assess and document positive or negative changes in the next decades.